Discriminatory analysis of anthropometric characteristics in young swimmers - Ostrowska, B.; Domaradzki, J.; Rozek-Mróz, K. (Medicina Sportiva, 2005)
The aim of this study was to describe the set of somatic characteristics, which significantly discriminate young swimmers. Methods: 160 pupils (11 and 12-year-old) from primary schools in Wroclaw were recruited for the study. The research group (Group I) consisted of swimmers and the comparative group (Group II), the non-swimmers. The participants selected for the study had been involved in swimming for 2 - 3 years. On average their training time per week was 12 to 18 hours. The following parameters were established: body height and weight, upper and lower extremities length, circumferences of: thighs, shanks, arms, forearms, chest at rest, chest after inspiration, chest after expiration, waist, hips, shoulder width, hip width, chest width, chest depth, and Rohrer index. In order to accomplish the aim of the study, a discrimination analysis method was employed. Results: Analysis of the results indicated that the model for boys significantly appeared to discriminate the studied groups. The parameters, which distinguish the groups to the largest degree, include circumferences of the body, length parameters, and hip width. Those parameters indicate formation of the body figure typical for swimmers, characterized by specific proportions of the chest and hips, and usually by longer limbs. The difference in muscles circumferences is a direct result of training. This diversity between the groups of girls is less significant. This indicates that physical training influences the female body figure to a smaller degree than that of males. The parameters which discriminate girls the most, are the circumference of the thigh and shank, the hip width and the chest depth. Conclusions: Sport training decreases dysmorphic differences and increases similarities in the constitution of boys and girls.